2018
DOI: 10.1680/jgein.18.00020
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of adjacent strip footings on reinforced soil using upper-bound limit analysis

Abstract: This paper explores the ultimate bearing capacity of two closely spaced interfering strip footings resting on a reinforced cohesionless soil bed using upper-bound limit analysis. The soil is assumed to follow the Mohr-Coulomb failure criteria along with the associated flow rule. A kinematically admissible multi-block failure mechanism is adopted in the analysis. The effect of interaction is studied with respect to angle of internal friction of soil (ϕ), clear spacing between the footings (s) and the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The bearing capacity of the left footing when N = 1 increases from 104 to 185%, with a decrease in the depth of footing embedment from D f /B L = 1,0 to 0,25. The improvement in the ultimate bearing capacity for symmetrical interfering footings in a soil medium reinforced with N-layers of geosynthetic material is evident in earlier research on surface footings (Ghazavi and Lavasan, 2008;Lavasan et al, 2017;Biswas and Ghosh, 2018) and embedded footings (Ekbote and Nainegali, 2019a), which holds true in the case of asymmetric footings. However, r ,max L ξ is higher than r ,max R ξ .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The bearing capacity of the left footing when N = 1 increases from 104 to 185%, with a decrease in the depth of footing embedment from D f /B L = 1,0 to 0,25. The improvement in the ultimate bearing capacity for symmetrical interfering footings in a soil medium reinforced with N-layers of geosynthetic material is evident in earlier research on surface footings (Ghazavi and Lavasan, 2008;Lavasan et al, 2017;Biswas and Ghosh, 2018) and embedded footings (Ekbote and Nainegali, 2019a), which holds true in the case of asymmetric footings. However, r ,max L ξ is higher than r ,max R ξ .…”
Section: Resultsmentioning
confidence: 81%
“…Many researchers have studied the problem by performing small-scale laboratory or field tests, as well as by conducting theoretical or numerical analyses on an unreinforced soil medium. These studies have implemented different theoretical or numerical techniques, such as a method of stress characteristics (Graham et al, 1984;Kumar and Ghosh, 2007a); upper bound limit analysis (Kumar and Kouzer, 2008;Kumar, 2008, 2010;Kumar and Ghosh, 2007b;Yang et al, 2017;Biswas and Ghosh, 2018;Keawsawasvong et al, 2021;Yodsomjai et al, 2021); lower bound limit analysis Bhattacharya, 2010, 2013;Shiau et al, 2021;Keawsawasvong and Boonchai Ukritchon, 2022); the finite difference method (Ghazavi and Lavasan, 2008;Ghosh and Sharma, 2010;Mabrouki et al, 2010;Lavasan and Ghazavi, 2012b;Javid et al, 2015;Lavasan et al, 2017); the finite element method (Lee et al, 2008;Lee and Eun, 2009;Kumar and Bhoi, 2010;Nainegali et al, 2013Nainegali et al, , 2018Nainegali et al, , 2019Noorzad and Manavirad, 2014;Zidan and Mohamed, 2019;Sekhar et al, 2020;Shokoohi et al, 2019;Fuentes et al, 2019;Ekbote and Nainegali., 2019a, b;Sekhar et al, 2020;Alzabeebee, 2020Alzabeebee, , 2022Ekbote et al, 2022); the analytical method Saran, 2003b, 2004;Ghos...…”
Section: Introductionmentioning
confidence: 99%
“…Several reports are published after the pioneering work reported by Stuart [1] using different analytical/numerical methods and experimental observations. The studies offering the understanding of two or multiple interfering footings using analytical/numerical methods use upper and lower bound limit analysis [2][3][4][5][6][7], finite difference method [8][9][10], finite element method [11][12][13][14][15][16][17][18] and analytical method [19,20], the probabilistic method [21] and others [22]. Then several experimental studies [23][24][25][26][27][28][29] have been reported on the interference of surface footings.…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, geosynthetics have been extensively implemented all around the world for improving weak foundations, reinforcing critical slopes and retaining walls, coastal protection systems, and improving weak pavement layers, among many other applications ( 12, 1720 ). Both woven and non-woven geotextiles have been widely used for reinforcement and hydraulic applications in pavement design ( 17 ).…”
mentioning
confidence: 99%